2023
DOI: 10.1002/anie.202303817
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Interactions between Polyoxometalates and Proteins for Applications in (Bio)chemistry and Medicine

Abstract: The specific interactions of anionic metal-oxo clusters, known as polyoxometalates (POMs), with proteins can be leveraged for a wide range of analytical and biomedical applications. For example, POMs have been developed as selective catalysts that can induce protein modifications and have also been shown to facilitate protein crystallization, both of which are instrumental in the structural characterization of proteins. POMs can also be used for selective protein separation and enzyme inhibition, which makes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 140 publications
0
9
0
Order By: Relevance
“…[102][103][104][105][106][107][108][109][110] These interaction studies have shown that POM-protein binding is mainly driven by charge-charge and H-bonding interactions, although hydrophobic interactions and coordinative binding can also occur, especially with POMs functionalized with organic moieties and with M-POMs, respectively. [110][111][112][113] However, since POM-protein interactions and the hydrolytic activity of POMs towards proteins have been recently reviewed by our group, 24,58,111 this section will only briefly discuss the main conclusions obtained from these studies.…”
Section: (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…[102][103][104][105][106][107][108][109][110] These interaction studies have shown that POM-protein binding is mainly driven by charge-charge and H-bonding interactions, although hydrophobic interactions and coordinative binding can also occur, especially with POMs functionalized with organic moieties and with M-POMs, respectively. [110][111][112][113] However, since POM-protein interactions and the hydrolytic activity of POMs towards proteins have been recently reviewed by our group, 24,58,111 this section will only briefly discuss the main conclusions obtained from these studies.…”
Section: (E)mentioning
confidence: 99%
“…70,119 Furthermore, the electrostatic nature of POM-protein interactions means that they are significantly affected by the pH, ionic strength, and temperature. 58,111 The reactivity also depends on the speciation of M-POMs, which in turn depends on the ionic strength, concentration, temperature, dielectric constant, and pH of the medium. 58 Hence, the conditions used need to be carefully considered to optimize the hydrolytic activity.…”
Section: (E)mentioning
confidence: 99%
“…Polyoxometalates (POMs), as an excellent inorganic functional material with unique diversity structures and physical–chemical properties, exhibited outstanding performance in catalysis. Regrettably, bulk POMs with high solubility in polar media make it difficult to recover and recycle the catalysts, which limits their applications as heterogeneous catalysts. Notably, due to their oxygen-rich surface, high anionic charge, and diverse size, POMs can serve as inorganic building subunits to assemble with organic ligands and metal cations to achieve controlled assembly of POM-based compounds with fascinating structures and special properties. This provides an effective approach for the development of heterogeneous catalysts based on POMs. Benefiting from their facile preparation and relative stability, the well-known Keggin-type POMs, [PMo 12 O 40 ] 3– /[PW 12 O 40 ] 3– , have been extensively used as building subunits for the assembly of various POM-based compounds. On the other hand, as a d 10 metal cation, Ag + is easy to coordinate with N and O and has a variety of coordination modes, making it a good metal connector to construct POM-based compounds. For example, Wang’s group synthesized three POM-based metal–organic complexes using H 3 PMo 12 O 40 (K 6 P 2 W 18 O 62 ·15H 2 O), Ag + , and bis­(pyridyl-tetrazole) ligands and studied their fluorescence properties, electrochemical behaviors, and photocatalytic activities .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional noble metal catalysts (e.g., Pt, Rh, and Ir and their oxides) , are too expensive for large-scale applications . To lower the cost, earth-abundant transition-metal-based compounds have been explored extensively. Among different materials, polyoxometalate (POM) compounds exhibit a wide variety of elemental compositions and versatile molecular structures, leading to their interesting physical and chemical properties. ,, Among many types of POMs, the Wells–Dawson type, with the general formula [X 2 M 18 O 62 ] n − , has been widely exploited for PC water splitting reactions because of their ease of synthesis and unique chemical/electron-transfer properties. For example, Duan and co-workers have reported a variety of Wells–Dawson-type POMs embedded in the pores of REDOX-active coordination polymers or other material matrixes for PC hydrogen evolution. , They have shown that the Dawson-type P 2 W 18 polyanion plays a key role in affecting the rate of hydrogen evolution by synergistically interacting with other substances.…”
Section: Introductionmentioning
confidence: 99%